2021
DOI: 10.1057/s41287-021-00408-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Accountability Undermine Service Delivery? The Impact of Devolving Agriculture in Ghana

Abstract: In recent years, many developing countries have devolved services to locally elected governments. Although this may strengthen downwards accountability to citizens, does devolution improve service provision? Ghana began devolving agriculture in 2012 to its Metropolitan, Municipal, and District Assemblies (MMDAs). Drawing on an original survey with 80 District Directors of Agriculture and 960 households, as well as district-level budget data and interviews with national and local government stakeholders, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Pada dasarnya, akuntabilitas menuntut pejabat pemerintah untuk menjelaskan tindakan mereka kepada publik dan disertai dengan beberapa bentuk penegakan untuk menghukum kinerja yang buruk. Dengan rasa kepemilikan tanggung jawab penyediaan layanan kepada masyarakat, pemerintah memiliki prioritas penuh untuk warganya (Resnick, 2022).…”
Section: Pendahuluanunclassified
“…Pada dasarnya, akuntabilitas menuntut pejabat pemerintah untuk menjelaskan tindakan mereka kepada publik dan disertai dengan beberapa bentuk penegakan untuk menghukum kinerja yang buruk. Dengan rasa kepemilikan tanggung jawab penyediaan layanan kepada masyarakat, pemerintah memiliki prioritas penuh untuk warganya (Resnick, 2022).…”
Section: Pendahuluanunclassified
“…Political decentralisation aims to ensure democratic local governance by giving local people and their elected leaders more influence in policy formulation and implementation for their social, political, and economic well-being (Resnick, 2021). Smoke (2003) opines that administrative and fiscal decentralisation are important but cannot achieve the needs of decentralisation and local government reforms in general without adequate political reform.…”
Section: Political Centralisationmentioning
confidence: 99%
“…The low visibility of agricultural extension reflects the fact that it involves the transfer of an intangible item, i.e., knowledge, its benefits are only evident in the longer-term, and attribution is difficult, since the benefits of extension advice can be undermined by bad weather, economic shocks, or improper implementation by smallholders (Anderson 2008). PIM-supported surveys of rural households in Ghana (Resnick 2021) and Nepal (Kyle et al 2017) revealed that, despite low levels of access to extension services, those employed in Relatedly, it can be difficult to gain traction among policymakers for complex, long-term, and/or multisectoral interventions. For example, in Bangladesh and India, PIM researchers examined the prospects for implementation of weather indexbased crop insurance for smallholder farmers.…”
Section: Nature Of the Policymentioning
confidence: 99%